2014
DOI: 10.1149/06201.0247ecst
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Distribution in Monocrystalline Silicon-Based Lithium-Ion Batteries

Abstract: The ability of nitrides and alloys of refractory metals to act as solid-state diffusion barrier for Li migration in Si was evaluated by mass spectrometry techniques. Magnetron sputtered barrier films on silicon, assembled in a Swagelok® half-cell, were used as working electrodes to determine whether several barrier layers are able to prevent the formation of Li-Si alloys. In addition, lithium ion diffusion was studied in monocrystalline silicon. To determine the depth profiles in the silicon substrate and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The developments of microelectronics and MEMS (microelectro-mechanical systems) demand micro-sized on-board power sources for establishing an autonomous microsystem. [1][2][3][4][5] A thin-lm lithium-ion battery (LIB) is promising for on-board power supply because of its high energy and power densities. Compared with the conventional carbon anode (ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The developments of microelectronics and MEMS (microelectro-mechanical systems) demand micro-sized on-board power sources for establishing an autonomous microsystem. [1][2][3][4][5] A thin-lm lithium-ion battery (LIB) is promising for on-board power supply because of its high energy and power densities. Compared with the conventional carbon anode (ca.…”
Section: Introductionmentioning
confidence: 99%
“…4200 mA h g À1 ). [4][5][6][7][8][9][10][11][12][13] Moreover, Si-based materials (e.g. Si, silicon oxide, silicon nitride and silicon carbide) are widely used in microelectronics; consequently, LIBs with Si-based materials as the anode are easy to integrate with electronic and MEMS devices.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize the material properties and processing conditions of functional battery layers, knowledge about the lateral and vertical distribution of lithium is crucial. By analyzing the lithium depth distribution of electrode or electrolyte layers, one can, for example, investigate the impact of different processing parameters on the elemental composition of battery components [1,2] or visualize the interdiffusion of lithium between active layers and inactive components of batteries [3,4]. An even more fundamental field of application is the analysis of cycled battery cells in different states of charge, to get a deeper understanding of the Li transport and the de-/intercalation process inside the functional layers of the battery [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Driven by these difficulties in detection and quantification of lithium, an innovative combined approach is introduced, where Time of Flight -Secondary Ion Mass Spectrometry (ToF-SIMS) and Glow Discharge Optical Emission Spectroscopy (GDOES) are used to characterize the depth profile of Li distribution in LiCoO 2 (LCO) thin films prepared by unbalanced radio frequency magnetron sputtering. The capability of ToF-SIMS to detect the spatial lithium distribution with high sensitivity makes this technique an ideal candidate for the investigation of thin functional layers in batteries [4][5][6][7][8]. As a reference, GDOES is used as independent comparative analytical techniques for the lithium depth profile analysis, and to evaluate potential measurement artefacts of the ToF-SIMS analysis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ullrich Steiner et al have made great achievements in the research of inverse opal vanadium oxide films, 9 enhanced electrochromism in gyroid-structured vanadium pentoxide 10 and the extended application in the field of supercapacitors. 11 However, until now very few studies have reported on the inorganic monolithic all-thin-film device durability as lithium [18][19][20][21] makes this technique a perfect candidate for the investigation of functional layers in devices. A few earlier studies tried to detect the remaining lithium by SIMS but were only limited to EC single layer WO 3 and V 2 O 5 .…”
Section: Introductionmentioning
confidence: 99%